2022
DOI: 10.3390/ma15030785
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Microstructure, Texture, and Mechanical Properties of TZ61 and AZ61 Mg Alloys Processed by Differential Speed Rolling

Abstract: In this work, the comparison of microstructure, texture, and mechanical properties of the newly developed TZ61 (Mg-6Sn-1Zn) alloy with the commercially available AZ61 (Mg-6Al-1Zn) has been presented. Both analyzed Mg alloys were processed by conventional symmetric and asymmetric rolling (i.e., Differential Speed Rolling—DSR). The microstructure and texture were examined by EBSD and XRD, whereas the mechanical behavior was investigated by uniaxial tensile tests. DSR processing led to more effective grain refine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Roll pressures are substituted into Equations ( 24)- (26). Integration gives the roll force per unit width for different deformation region states as follows:…”
Section: Roll Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Roll pressures are substituted into Equations ( 24)- (26). Integration gives the roll force per unit width for different deformation region states as follows:…”
Section: Roll Forcementioning
confidence: 99%
“…Xiao et al [25] employed asymmetrical rolling to refine grains in order to investigate the mechanical properties of pure titanium foils. By comparing the microstructure, texture, and mechanical properties of TZ61 and AZ61, Majchrowicz et al [26]. found that the plasticity of annealed TZ61 and AZ61 sheets increased because of the reduced grain size and weakened basal texture caused by the asymmetric rolling process.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the various excellent properties such as high specific strength, good corrosion resistance, superior stability in broad temperature range, and good weldability, titanium and titanium alloys have been widely used as important structural materials in aerospace, marine, biomedical engineering, and other high-tech fields. [1][2][3][4][5][6] Two-phase titanium alloys, such as Ti-6Al-4 V, Ti-6.5Al-2Zr-1Mo-1 V, and Ti-5Al-2Sn-2Zr-4Mo-4Cr, are mainly composed of low-temperature stable α phase and hightemperature stable β phase. [7] Ti-6Al-2Sn-4Zr-6Mo (Ti6246) is also a typical α þ β two-phase titanium alloy, which was developed in the United States in the 20th century by modifying the Ti-6Al-2Sn-4Zr-2Mo alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Mg is strengthened by additives [3][4][5], heat, and plastic treatment [6], e.g., ECAP technology [7,8]. Numerous alloys are formed based on a Mg matrix, and the most frequently tested magnesium alloys include AZ31, ZE41, AZ61, AM60, AZ61, AZ80, and AZ91 [9][10][11][12][13][14][15][16][17]. The most common methods used to produce elements from Mg alloys are cast, die-cast [18], cast-rolling [19], rolling [20], squeeze cast [21], and extrusion [10,22,23].…”
Section: Introductionmentioning
confidence: 99%